Phytochemical analysis of Cagaita (Eugenia dysenterica DC) leaf extracts in Northern Minas Gerais Cerrado, Brazil - ALMEIDA, Ramine Mirelle Mendes Pereira; OLIVEIRA, Mariuze Loyanny Pereira; VIEIRA, Cláudia Regina; PAIVA, Caroline Liboeiro; BRANDI, Igor Viana; COSTA, Theles de Oliveira; SANTOS, Daniela Cácia dos; MENDES, Ludmila Ribeiro (Food Science and Technology, 2025)
The objective of this study was to perform a phytochemical screening of the aqueous extracts of the leaves of Eugenia dysenterica DC to identify the secondary compounds present; evidence the presence of total yellow flavonoid compounds; identify total phenolic compounds, evaluate antioxidant activity; and verify the influence of the different extraction methods on the concentration of the identified secondary metabolites. For phytochemical evaluation, three aqueous extracts were obtained using infusion, decoction, and maceration. The preparation followed the methodology of Garlet (2019), with adaptations. The phytochemical screening included the determination of the total phenolic content by the FolinCiocalteu method. Absorbance was measured spectrophotometrically. Antioxidant activity was determined by oxygen radical absorption capacity method described by Prieto et al. (1999). The determination of yellow flavonoids was performed as described by Francis (1982), with modifications. Maceration was the most effective method to extract total yellow flavonoids, while decoction was the most effective to extract total phenolic compounds. Maceration resulted in higher antioxidant activity. Statistical differences indicate that the choice of extraction method should be guided by the type of bioactive compound of interest and its thermal stability to maximize the extraction of certain secondary metabolites from Eugenia Dysenterica DC.